2000
DOI: 10.2135/cropsci2000.4041168x
|View full text |Cite
|
Sign up to set email alerts
|

Level and Geographical Distribution of Resistance to Meloidogyne arenaria in the U.S. Peanut Germplasm Collection

Abstract: The peanut root‐knot nematode [Meloidogyne arenaria (Neal) Chitwood race 1] causes significant economic losses in many peanut (Arachis hypogaea L.) production areas of the world. The objectives of this study were (i) to examine the peanut core collection to identify sources of resistance, (ii) to estimate the level of resistance that occurs in the U.S. germplasm collection, and (iii) to examine the geographical distribution for resistance in peanut germplasm. Seven hundred forty‐one accessions from the core co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 10 publications
3
33
0
Order By: Relevance
“…These 11 sources ofresistance were greater than what would be expected based on the frequency of accessions from China in the entire collection. We have previously reported that China appears to be valuable geographical sources of resistance to this nematode (Holbrook et al, 2000a). Second-stage screening of selected groups of accessions from the entire germplasm collection confirmed that observation (Holbrook et al, 2000b).…”
Section: Resultssupporting
confidence: 66%
“…These 11 sources ofresistance were greater than what would be expected based on the frequency of accessions from China in the entire collection. We have previously reported that China appears to be valuable geographical sources of resistance to this nematode (Holbrook et al, 2000a). Second-stage screening of selected groups of accessions from the entire germplasm collection confirmed that observation (Holbrook et al, 2000b).…”
Section: Resultssupporting
confidence: 66%
“…are the most frequently observed biotrophic nematode parasites in plants, with a broad host range of more than 2000 species, including many crops (Agrios 2005). These nematodes are obligate endoparasites that occur in tropical and temperate regions, and cause significant economic losses in peanut production areas worldwide (Holbrook et al 2000). The most widely used strategy to control root-knot nematodes is the use of nematicides, which are often highly toxic and have been progressively restricted or banned due to environmental and human health concerns (Collange et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hence screening of various germplasm sets, such as core and mini core collection accessions, is important for the identification of resistant sources. Previous researchers have demonstrated that valuable genes in germplasm collections can be effectively identified by using a core or mini core collection (Anderson et al 1996a;Franke et al 1999;Holbrook and Anderson 1995;Holbrook et al 2000a;Isleib et al 1995). Mini core germplasm accessions have been widely screened in several crops, including groundnut, for identifying resistant sources to different biotic (Kusuma et al 2007) and abiotic stresses (Vadez et al 2007).…”
Section: Discussionmentioning
confidence: 99%